Comparison of velocity-based & traditional resistance exercise training - Pelka, E. Z.; Claytor, R. (ISBS Proceedings Archive (Michigan), 2019)
This study compared the effects of 4 weeks (8 training sessions) of velocity-based resistance exercise (RE) training (VBT) and Traditional RE training (Trad) on maximal muscular strength (1-RM), total load (TL), total RE time (TT) and rating of perceived exertion (RPE) across days of training. Thirty-eight individuals (20 females & 18 males) were randomly assigned to VBT or Trad for 1 leg-leg extension RE training study. The VBT completed 3 sets of reps until velocity decreased by 20%; Trad completed 3 sets of 12 repetitions or until failure. TL, TT and RPE were significantly lower across days of training for VBT, while 1-RM increased significantly and similarly for both groups and males and females. These data suggest VBT provokes a similar increase in muscular strength with less TL (work), TT and effort (RPE) during a short-term training study.